On the genus "Asplenium" in the Iberian Peninsula" - Sleep, A. (Universidad de Málaga, Servicio de Publicaciones, 1983)
The Asplenium species recorded from the Iberian peninsula comprise diploids and tetraploids, and of the latter, both auto- and allotetraploids occur. Evidence from the meiotic pairing behaviour of the chromosomes in synthetic hybrids is adduced to show how the mode of origin and interrelationships of such species can be elucidated, and specific reference is made to Asplenium foresiense, A. majoricum, A. petrarchae and A. billotii. The suggested occurrence of autopolyploidy in Asplenium cuneifolium is also discussed. Evidence is presented which shows that in the British Isles and Corsica serpentine plants previously regarded as autotetraploid derivatives of A. cuneifolium are in fact allotetraploid and almost certainly just specialized serpentine forms of Asplenium adiantum-nigrum. It is suggested that such forms of A. adiantum-nigrum could occur also on serpentine rocks elsewhere in western Europe, for example, in Spain and France.

Las especies del genero Asplenium, registradas en la Peninsula Ibérica, comprenden citotipos diploides y tetraploides, siendo estos últimos tanto autotetraploides como alotetraploides. Del apareamiento miótico de los cromosomas en los híbridos sintéticos se aducen pruebas para mostrar como se pueden dilucidar el modo de origen y las interrelaciones de tales especies, y se hace referencia específica a Asplenium foresiense, A. majoricum, A. petrarchae y A. billotii. También se discute la cuestión de la autopoliploidía de A. cuneifolium que habia sido sugerida previamente. Se ofrecen datos experimentales que muestran que en las Islas Británicas y en Córcega las plantas que crecen sobre serpentinas, anteriormente consideradas como un derivado autotetraploidal de A. cuneifolium, son en realidad alotetraploides y, casi con certeza, no son más que formas serpentinícolas especializadas de A. adiantum-nigrum. Se sugiere que tales formas de A. adiantum-nigrum pueden existir también sobre serpentinas en otras partes de Europa occidental, por ejemplo, en España o Francia.